Effect Of Profitability, Liquidity, Share Ownership Structure, Leverage, and Capital Intensity on Tax Aggressiveness (Empirical Study of Mining Companies Listed on the IDX in 2016-2020): Pengaruh Profitabilitas, Likuiditas, Struktur Kepemilikan Saham, Leverage, dan Capital Intensity Terhadap Agresivitas Pajak (Studi Empiris Perusahaan Pertambangan yang Terdaftar di Bei Tahun 2016-2020) - Annastasari, Meutia Salma; Aris, Muhammad Abdul (Procedia of Social Sciences and Humanities, 2022)
This study aims to analyze the effect of profitability, liquidity, share ownership structure, leverage, and capital intensity on tax aggressiveness in mining companies listed on the Indonesia Stock Exchange in 2016-2020. The population used in this study are all mining companies listed on the Indonesia Stock Exchange in 2016-2020. The research sampling method used purposive sampling and obtained as many as 15 mining companies that met the criteria with a total of 75 data samples. Because there are 7 sample data that have outliers, the number of samples in this study is 68 data. The data analysis method used is multiple linear regression analysis with the help of SPSS 26 application. The results of this study indicate that partially profitability and capital intensity variables have a significant effect on tax aggressiveness, while liquidity, share ownership structure, and leverage variables have no significant effect on tax aggressiveness. Simultaneously the variables of profitability, liquidity, share ownership structure, leverage, and capital intesnity have a significant effect on tax aggressiveness.